Patterns of Posidonia oceanica (L.) Delile tannin cells and leaf characteristics according to environmental conditions - BOUMAZA, SALIMA; SENGOUGA, AMINA; GASMI, DJIHAD; MISRAOUI, ALI; PERGENT, GERARD; SEMROUD, RACHID (Mediterranean Marine Science, 2022)
There is little research on the distribution and evolution of tannin cells, specialized in the sequestration of phenolic compounds, in the leaves of P. oceanica, depending on the developmental stage and environmental conditions. This work aims to evaluate the density of tannin cells along the vertical axis of leaves (basal, middle, and apical regions) at four sites corresponding to an anthropogenic gradient estimated from the ecological status of P. oceanica meadows: Moderate (El Djamila), Good (Bou Ismaïl) and very good (Kouali and Aïn Tagouraït). Leaf thickness and width were measured in each region to express the density of tannin cells per mm². Data analysis shows that the density of tannin cells decreases with increasing leaf age and that the highest densities are recorded in the apical regions, especially when the leaf apex is entire. The density of leaf tannin cells is significantly correlated (R = -0.977, p = 0.022) with the Ecological Quality Ratio (EQR) corresponding to the ecological status of P. oceanica meadows and reflecting the impact of environmental pressures. This sensitivity to environmental conditions opens interesting prospects for using tannin cell density as a descriptor (environmental biomarker) in coastal monitoring programs based on P. oceanica meadows.